2020
DOI: 10.1017/s0031182020002243
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in helminth infections of wood mice (Apodemus sylvaticus) from the vicinity of Malham Tarn in North Yorkshire, England

Abstract: Helminth infections in wood mice (n = 483), trapped over a period of 26 years in the woods surrounding Malham Tarn in North Yorkshire, were analysed. Although 10 species of helminths were identified, the overall mean species richness was 1.01 species/mouse indicating that the helminth community was relatively depauperate in this wood mouse population. The dominant species was Heligmosomoides polygyrus, the prevalence (64.6%) and abundance (10.4 worms/mouse) of which declined significantly over the study period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 72 publications
(139 reference statements)
3
11
0
Order By: Relevance
“…The values obtained in the burned area are very similar to those reported in other studies on the wood mouse in the Iberian Peninsula [39,42], being slightly higher than those reported in the burned area of previous periods analysed [14,17]. However, the values in the burned area are higher than those obtained in other wood mouse studies such as a long-term study carried out during 26 years in England, which reported an overall mean species richness of only 1.01 [26].…”
Section: Mean Species Richnesssupporting
confidence: 83%
See 3 more Smart Citations
“…The values obtained in the burned area are very similar to those reported in other studies on the wood mouse in the Iberian Peninsula [39,42], being slightly higher than those reported in the burned area of previous periods analysed [14,17]. However, the values in the burned area are higher than those obtained in other wood mouse studies such as a long-term study carried out during 26 years in England, which reported an overall mean species richness of only 1.01 [26].…”
Section: Mean Species Richnesssupporting
confidence: 83%
“…Among the influences exercised by the climate on the species richness, the positive correlation of mean temperature and rainy days in the burned area only stands out. The logical and predictable influence of the host age on the species richness has also been reported in other peninsular enclaves, such as the Erro river valley [42] and Sierra Espuña [39], and in England [26], as well as in the burned area, but also in the control area in previous periods analysed in Serra Calderona NP, i.e., in the 2nd-10th PFY period [17].…”
Section: Mean Species Richnesssupporting
confidence: 62%
See 2 more Smart Citations
“…Moreover, older animals are more likely to be infected given their age and having covered more territory to come into contact with infective forms [ 53 ]. Prevalence and intensity of helminth parasites increase with host age in other studies with wild rodents [ 19 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. In C. minutus , the results were those to be expected.…”
Section: Discussionmentioning
confidence: 80%